2020
DOI: 10.1002/bies.202000115
|View full text |Cite
|
Sign up to set email alerts
|

The circle of Willis revisited: Forebrain dehydration sensing facilitated by the anterior communicating artery

Abstract: We hypothesize that threat of dehydration provided selection pressure for the evolutionary emergence and persistence of the anterior communicating artery (ACoA – the inter‐arterial connection that completes the Circle of Willis) in early amniotes. The ACoA is a hemodynamically insignificant artery, but, as we argue in this paper, its privileged position outside the blood‐brain barrier gives it a crucial sensing function for the osmolarity of the blood against the background of the rest of the brain, which effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 95 publications
0
11
0
Order By: Relevance
“…Taken as a whole, the particularities of the vascular architecture highlighted in the compared species would be considered morphological variations throughout the phylogeny (De Vriese et al, 1984;Gillilan, 1972), rather than evolutionary adaptations per se (Matsuo, 2012). Therefore, the general architecture of vessels would have emerged by convergent evolution at the suborder level (Fenrich et al, 2021;Vrselja et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Taken as a whole, the particularities of the vascular architecture highlighted in the compared species would be considered morphological variations throughout the phylogeny (De Vriese et al, 1984;Gillilan, 1972), rather than evolutionary adaptations per se (Matsuo, 2012). Therefore, the general architecture of vessels would have emerged by convergent evolution at the suborder level (Fenrich et al, 2021;Vrselja et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The high level of structural conservation of the CoW among species established the classic notion of this structure as a safe brain circulation system capable of ensuring the blood flow to the brain in case of obstruction of the internal carotid artery of one hemisphere through the contralateral blood supply by the rostral communicating artery (Goswami et al, 2020; Snell, 2007). However, its function has recently been reviewed due to the very low frequency of stenosis observed in non‐human species (Fenrich et al, 2021; Vrselja et al, 2014) and the structural vascular studies that focus on variations in CoW among species (Aydin et al, 2008; Fenrich et al, 2021; Kuchinka, 2017; Okuyama et al, 2004; Sasahara et al, 2020). Preliminarily, all these results point to a passive system for dissipating pressure and energy as the main function of the CoW as discussed in Burlakoti et al (2017) and Vrselja et al (2014) rather than a safety system as was established by Thomas Willis, 400 years ago.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other than naming the arteries forming the cerebral arterial circle, the authors gave little information on the intracranial vasculature of the Baikal ringed seal (Frąckowiak & Godynicki, 1996), preventing detailed comparisons between ring seal subspecies. The rostral communicating artery was reported to be variably present in Carnivora (ICVGAN 2017; Tanaka et al, 2018) and indicated as being involved in the forebrain dehydration sensing (Fenrich et al, 2021), was not present in any of the Saimaa or Baltic ringed seal specimens. Water balance is not an issue for freshwater seals with easy access to drinking water.…”
Section: Discussionmentioning
confidence: 99%